2. ASSESSMENT OF THE QUALITY OF LIFE OF CHILDREN 6-14 YEARS OLD WITH ALLERGIC INFECTION AT NATIONAL CHILDREN'S HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the quality of life score of a 6-14 year old pediatric patient with allergicrhinitis. Methods: A cross-sectional descriptive study on 855 children 6-14 years old with allergicrhinitis, using the PRQLQ scale. Results: The average total quality of life score according to thePRQLQ scale was 77.44±19.32, of which the highest was 125 points and the lowest was 14 points.In addition, there was a statistically significant relationship between the severity of the disease overtime and the severity of the quality of life score (p
Keywords: Allergic rhinitis, quality of life, children.